The Indispensable Community: Why Some Brand Communities Thrive When Others Perish - and Millington, Richard (Feverbee, 2018)
How to Build Bigger, Better, and More Active Online CommunitiesBuzzing Communities cuts through the fluff to offer a clear process for creating thriving online communities. This book combines a century of proven science, dozens of real-life examples, practical tips, and trusted community-building methods. This step-by-step guide includes a lifecycle for tracking your progress and a framework for managing your organization's community efforts. This Book Will Help You to Understand what the members of your community really want. Dramatically increase the number of newcomers that become regulars. Avoid the mistakes most organizations make when they try to build online communities. Develop a fantastic, user-friendly website for your members. Grow your online community to critical mass and beyond Keep members engaged and active in your community. Measure the community's return on investment and explain the benefits to your organization.